Pemetaan Profil Anak Berkebutuhan Khusus di PAUD dan Implikasinya dalam Pendekatan Child-Centered Learning - Al Baqi, Safiruddin (Nak-Kanak: Journal of Child Research, 2024)
Children with special needs often require tailored learning methods to support their cognitive, physical, sensory, social-emotional, and behavioral development. Despite the importance of inclusivity in education, early childhood education (ECE) institutions face challenges in creating effective and inclusive learning environments due to limited resources, inadequate teacher training, and a lack of adaptive curriculum frameworks. Understanding the specific needs of these children through detailed profiles can help guide teaching practices and support their academic and social-emotional growth. This research aims to map the profiles of children with special needs in ECE based on a comprehensive literature review and analyze how these profiles can inform child-centered educational approaches. Using a library research methodology, the study synthesizes information from books, academic journals, and other relevant sources to build a comprehensive profile of common special needs categories in ECE. The findings reveal patterns in the prevalence of specific needs and highlight early indicators of developmental challenges. The study emphasizes the need for a responsive and inclusive educational environment, where teaching methods are adapted to meet the unique needs of each child. Recommendations include targeted training for educators on adaptive teaching strategies and inclusive classroom management, as well as advocating for resource allocation to improve supporting infrastructure. Additionally, the study suggests that policymakers consider using profiling tools as an essential component of early childhood education, enabling early identification and support for children with special needs. By integrating these practices, ECE institutions can enhance educational outcomes for all students, fostering a more inclusive learning culture that benefits children with diverse developmental needs.